2017
DOI: 10.1088/1742-6596/938/1/012071
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of fullerite of various composition

Abstract: Abstract. Molecular dynamics simulation is used to study the structures of fullerite of various composition as well as their mechanical properties. Fullerites based on fullerene C 60 with simple cubic and face-centered packing, fullerene-like molecule C 48 and fullerene C 240 with simple cubic packing are studied. Compliance and stiffness coefficients are calculated for fullerites C 60 and C 48 . For fullerite C 240 , C 60 , and C 48 , deformation behavior under the effect of hydrostatic compression is also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This dense feature of carbon in CS-DPAN results in unprecedently high tap density for the CS-DPAN composite (≈1.02 g cm −3 ), which was far improved compared to that of the value for the S-DPAN sample (≈0.89 g cm −3 ) was improved to for (Figure S4, Supporting Information). Because fullerite, C 60 , usually has a high tap density of ≈1.95 g cm −3 , [57] it is expected to resolve the main drawback of flaky S-DPAN that results in low energy density. In addition, CHNS analysis confirmed that the as-prepared CS-DPAN composite was composed of ≈57 wt% sulfur, 13 wt% nitrogen, and 30 wt% carbon.…”
Section: Resultsmentioning
confidence: 99%
“…This dense feature of carbon in CS-DPAN results in unprecedently high tap density for the CS-DPAN composite (≈1.02 g cm −3 ), which was far improved compared to that of the value for the S-DPAN sample (≈0.89 g cm −3 ) was improved to for (Figure S4, Supporting Information). Because fullerite, C 60 , usually has a high tap density of ≈1.95 g cm −3 , [57] it is expected to resolve the main drawback of flaky S-DPAN that results in low energy density. In addition, CHNS analysis confirmed that the as-prepared CS-DPAN composite was composed of ≈57 wt% sulfur, 13 wt% nitrogen, and 30 wt% carbon.…”
Section: Resultsmentioning
confidence: 99%